Effect of Full and Half MS-Salt Strength on Some Commercial Cultivars of Carnation (Dianthus caryophyllus L.) - Salam, Fathia Mohamed Noman; Alhadi, Fatima Ahmed; Al-Thobhani, Mansoor Abdalhaleem (PSM Biological Research, 2021)
This study was conducted to evaluate the effect of full and half-salt concentrations in Murashige and Skoog (MS) medium containing cytokinin (1mg/L Kinetin), auxin (0.1mg/L NAA) and 20gm/L sucrose, on four commercial cultivars of carnation " Gigi, Saeb, Morgan, and Salem". Single nodes were used as a source of explants (greater than or equal to) 1 cm long to determine the best MS-salt level that gives up the highest multiplication rate (Time of bud initiation, number of shoots, length of shoot, and number of leaves/shoot) and to determine the cultivar that will show the best proliferation rate. After four weeks of consecutive sub-culturing, the multiplication rate features were recorded. Full MS-salt strength gave a significantly higher number of shoots (1.9±0.14), length of shoots (2.69±0.20 cm), and the number of leaves/shoot (7.10±0.54) as compared to the half MS-salt strength (1.56±0.89, 2.00±0.12, and 4.29±0.26, respectively). However, the two salt levels showed no significant difference in the time of bud initiation. Moreover, the cultivar Salem exhibited maximum records in the length of shoots (4.25±0.36 cm), and the cultivar Gigi produced superior number of shoots (2.5±0.34), and they both exhibited the highest number of leaves/shoot (8.42±1.39; and 8.5±0.85, respectively) on full MS-salt strength. It is concluded that for micropropagation of carnation, full MS-salt strength is better than half MS-salt strength, and the cultivars Salem and Gigi are more responsive to the micropropagation on full MS-salt strength than the cultivars (Saeb and Morgan).